Concepts and practices of Halalan Tayyiban in the Islamic Manufacturing Practice (IMP): an analysis from Syariah perspective / Fakhri Sungit ... [et al.] - Sungit, Fakhri; Mohd Deni, Mohd Isa; Abdullah, Marliana; Abd. Ghani, Nurhayati; Syahwahid, Farah (Universiti Teknologi Mara Cawangan Pulau Pinang, 2020)
In Malaysia, halalan tayyiban has been conceptually practiced through the implementation of halal standards and enforcement of halal certification to ensure all Muslim would excess halal food. However, there is Muslim community which put the high standards of halalan tayyiban by designing the guidelines of manufacturing practice namely Islamic Manufacturing Practice (IMP). They emphasizes that the term tayyiban must be analyzed from tasawwuf dimension which should not confined from fiqh dimension alone because all food taken will transform to flesh and blood of the Muslim. Therefore, any kind of food which is considered as halalan tayyiban must be clean and pure both physically and spiritually. This paper aims to discover the guidelines of IMP as well as to shed lights the interpretation of halalan tayyiban by Muslim scholars. As a qualitative research, it employs the content analysis from fiqh literatures concerning the principles of Islamic jurisprudence towards halal and haram in Islam. The result indicates that halalan tayyiban must be referred to the formative rules over the substances with the guidance of texts and maslahah-mafsadah outlook. In the context of halal industry, the guidelines of IMP are designed based on Islamic teaching but not practically realistic for mass production.